THE EFFECT OF FEEDING FROM FERMENTED RICE BRAN AT DIFFERENT DOSES ON THE GROWTH OF KOI FISH SEEDS - Rusmadania, Rizqi; Putri, Rizky Febriyani; Istyadji, Maya (Transpublika Publisher, 2022)
The production of alternative feeds as a substitute for commercial feeds is expected to reduce the cost of farmers, with fermentation techniques to improve feed nutrition so that it is better and more durable by utilizing rice bran. This study aims to find out the right dose of feed and find out the effect of feeding on the growth of koi fish seeds. The methods used are experimental and observation techniques. Data analysis techniques use SPSS. The results of the study on fish weight produced normally distributed data, homogeneous and there was also a real difference, namely in the treatment A, B, C and K can be seen the best treatment, namely in B (100% fermented rice bran feed). While the results of the study on the length of the fish produced normally distributed data, homogeneous and there was an influence, there was also a real difference, namely the best treatment, namely in B (100% fermented rice bran feed) with the best dose of 0.08gr. Based on the statement above, the fermentation of rice bran affects the growth of koi fish seed cultivation.